(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
This study investigated admission policies and academic achievement among male and female students of public universities in South-West Nigeria (2008-2012). The design encompasses descriptive, ex post facto and correlational types. The sample of the study consisted of 3000 males and 3000 females (400 level) students who graduated from both state and federal public universities, purposively selected for sampling.The only instrument consisted of record observation format to collect secondary data. Three research questions were raised and answered. The three hypotheses formulated were tested using t-test. The dependent variable was indicated by the academic achievement, moderating variable by gender, while the independent variable was indicated by the modes of admission. Findings show that the percentage academic achievement of male students admitted through post-UTME, ELDS and direct entry that had first class and second class upper was higher than their female counterparts whereas the percentage academic achievement of students admitted through merit that had first class was higher in female students than in male students. However, inferential analysis of the data indicated the differences are not statistically significant. The findings conclude that there was no consistent research evidence of the effects of gender difference on students’ academic achievement. What the universities need are resources for teaching and learning and conducive environment that will guarantee effective learning rather than differential admission process. Hence, efforts should be made by university authorities to ensure no student is discriminated against based on gender for admission but all students be treated the same way so as to produce good quality graduates.